High Temperature Corrosion of Inconel 600 in NaCl-KCl Molten Salts - G. Salinas-Solano; J. Porcayo-Calderon; J. G. Gonzalez-Rodriguez; V. M. Salinas-Bravo; J. A. Ascencio-Gutierrez; L. Martinez-Gomez (Advances in Materials Science and Engineering)
In this work the corrosion resistance of a high content nickel alloy, Inconel 600, was investigated in mixed NaCl-KCl salts at 700, 800, and 900°C for 100 hours in static air. Investigation was carried out using electrochemical techniques such as polarization curves, rest potential measurements, linear polarization resistance, and electrochemical impedance spectroscopy. Corroded specimens were analyzed by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS). Electrochemical measurements showed an increased degradation rate of Inconel 600 with increasing test temperature. SEM and EDS analysis show that the damage experienced by Inconel 600 is greater than that determined by electrochemical measurements. This damage was identified as internal corrosion due to the reaction of Cl2 with the alloying elements (Cr and Fe); however, at 900°C the internal damage was minor and it was associated with the nickel content in the alloy.